Solidaritas Yesus Terhadap Disabilitas: Suatu Implikasi Praktis Solidaritas Gereja Terhadap Kaum Disabilitas - Darius Darius; Filia Amelia Kasinda (SANCTUM DOMINE: JURNAL TEOLOGI, 2022)
Abstract Humans are social beings who need their neighbors, especially those with limitations. Bringing home and warmth to them in the form of solidarity is a form of recognition of their existence in the midst of society. The basis for the enactment of solidarity in Christianity is the example and teaching of Jesus. This needs to be implicated in the life of the Church today. Therefore, this study will examine Jesus' Solidarity for people with disabilities: a practical implication of church solidarity with people with disabilities. The research method used is a qualitative type with a literature approach, namely books, journals and other documents. The result of this study is, First The basis of solidarity in Christianity is the example and teaching of Jesus. Second, church attendance as a form of practical implication of Jesus' example and teaching in building solidarity for people with disabilities.